The Effectiveness of Promotion, Location and Brand Image on Motorcycle Purchase Decisions - Octavianti Purnama; Vivin Hanitha; Georgius Listen (eCo-Fin, 2019)
The purpose of this study was to determine the effect of location, promotion and brand image on purchasing decisions for Honda motorcycles in Tangerang. In this thesis, research was conducted on 100 respondents through the distribution of questionnaires. The method used in this research is descriptive method and qualitative method. Based on the answers to the questionnaire, raw data has been obtained which is then processed using SPSS version 24 so that it becomes useful data for this research. In addition to calculating the relationship between the independent variable and the dependent variable, this study also calculated the relationship between variables. The correlation of the influence of location on purchasing decisions is0.484, the correlation of the effect of promotion on purchasing decisions is 0.432 and the correlation of the influence of location on purchasing decisions is0.167,so it can be said that the relationship between the four variables is quite strong. From the results of the F test model 1, the value of346,211,model 2 is rated461,897 and model 3 got a value of 593,825 where the value is greater than F table by 3.09, Thus Ho is rejected and Ha is accepted. In the t-test, the results of the t-count image can be obtainedbrand as big as 3,438t calculate the promotion of 6,181and t calculate the location of 7,710, when compared with a t table of 1,984then there is a significant relationship between brand image, promotion and location on purchasing decisions Honda motorcycles at PT. Tangerang Highlands Rides.